Effects of intensity and seasonal timing of disturbances on a rocky intertidal benthic community on the southern coast of Korea. Issue 3 (6th March 2014) - Kim, Sangil; Kang, Yun Hee; Choi, Chang Jae; Won, Nam‐Il; Seo, In‐Soo; Lee, Hyuk Je; Jung, Sukgeun; Park, Sang Rul
Abstract: The effects of intensity and timing of disturbances on recovery of marine benthic organisms were investigated on a rocky intertidal shore in Gwangyang Bay, Korea. We hypothesized that the recovery pattern of the benthic community structure would be affected by disturbance intensity and season. Twenty‐eight permanent plots were set up, with disturbance intensity (cleared plots and sterile plots) and seasonal disturbance (fall 1999 and spring 2000) incorporated into the experimental design. To monitor natural seasonal variation in benthic community abundances, we established seven permanent unmanipulated plots. Turf‐forming algae were observed in the unmanipulated plots throughout the experimental period, whereas green algae and invertebrate presence varied with season. In the disturbance‐intensity experiment, turf‐forming and green algae were dominant in cleared plots. The highest coverage of sessile organisms was observed in sterile plots, which exhibited the highest species richness because of their relatively low macroalgal coverage. Seasonal effects of disturbance were an important factor in the recovery pattern of benthic organisms under high disturbance intensity. Coverage of green algae was higher in sterile spring plots than in sterile fall plots; this result was attributed to low spatial competition, as the disturbances occurred just before green algal blooms. On the other hand, the abundances of barnacles and bivalves were highest on sterile fall plots, as these organisms were suppressed by green algal blooms in other periods. These results indicate that the effects of disturbance intensity on benthic community recovery patterns can be influenced by season of disturbance.